The use of the Decision Regret Scale in non-clinical contexts - Diotaiuti, Pierluigi; Valente, Giuseppe; Mancone, Stefania; Grambone, Angela; Chirico, Andrea; Lucidi, Fabio (Frontiers in Psychology, 2022)
The Decision Regret Scale (DRS) was assessed for its psychometric qualities in measuring decision regret in ordinary life scenarios. Although the scale has typically been used with patients and in the context of medical decision-making in earlier studies, this contribution shows that the instrument may have a variety of uses, retaining excellent metric properties even in non-medical contexts. The tool showed good fits with both the CFA and the gender Measurement Invariance. A non-probabilistic selection of 2,534 Italian university students was conducted. The internal consistency measures were found to be completely appropriate. Correlations with the General Decision-Making Style (GDMS) and Scale of Regulatory Modes were used to check for convergent validity (SRM). Convergence analysis showed that participants with higher regret scores were those who favored a rational decision-making style, while lower regret scores correlated with avoidant and spontaneous styles. With regard to the regulatory modes, the relationship between regret and locomotion was positive. Overall, the directions of association point to an interesting predictive measure of a person’s decision-making and self-regulatory orientation through the evaluation of regret using the DRS. The excellent psychometric properties found foreshadow a reliable use in various contexts where knowledge of post-decisional attitude becomes important: school, university, professional orientation, marketing studies, relationship choices, as well as for use in research.